Description of the larva of the Caucasian species Protonemura microstyla Martynov (Plecoptera, Nemouridae) - Zhiltzova, Lidia A. (Illiesia, 2012)
For the first time the larva of Protonemura microstyla Martynov is described from Caucasian material. It differs from the larva of P. bifida Martynov by very short blunt setae on pronotal margins and by a short pair of setae on thehind margin of abdominal tergites.
Keywords: entomology; Nemouridae; Plecoptera; Protonemura; larval description; Caucasus